Digital entrepreneurship: public perception of barriers, drivers, and future - Isabelle Biclesanu; Sorin Anagnoste; Ovidiu Branga; Marco Savastano (Administrative Sciences, 2021)
The widespread access to the Internet has undoubtedly changed the way businesses handle their processes and interact with their customers. With the surge of new devices, business models, technologies, and platforms, alongside social media growth and innovative advertising, it became easier to transition from employment to entrepreneurship. The paper aims to assess the public perception of digital entrepreneurship, with a focus on its barriers, drivers, and expectations for the future. The results show that there is a slight agreement with a digital business being easier to establish compared with a traditional one. The driving forces behind starting a digital business are recognized, and the digital environment is considered essential for business growth in the following years. With some exceptions, there are no significant differences between age groups, genders, relationship statuses, levels of education, and/or occupations when rating the barriers, drivers, and expectations for the future of digital entrepreneurship.
Keywords: 350; digital transformation; digital entrepreneurship; social media; e-business; e-commerce; online business; online platform; technology entrepreneurship